Design of hierarchical self-assembly 2D silica and their derivative catalysts with accessible open transport channels for boosting oxidative-adsorptive desulfurization in fuel oil. (15th September 2022) - Li, Feng; Zhou, Wending; Yang, Wanliang; Chen, Meili; Wang, Chun; Cao, Rui; Zhou, Chengliang
Graphical abstract: Hierarchical self-assembly 2D channel silica (2D-CSx ) and their derivative catalysts (2D-CSx -NH2 -HPW) were designed for boosting oxidative-adsorptive desulfurization (OADS) in fuel oil due to its accessible open transport 2D-channels contributed to molecular diffusions. Highlights: Hierarchical self-assembly 2D silica and their derivative catalysts were prepared. A novel theory of 2D SiO2 formed by curved-layered micelle stacking was proposed. The size and specific surface area of catalyst jointly determine its OADS performance. 2D-CS catalysts show the highest DBT removal rate than that of 0D and 1D materials. The accessible open transport 2D channels are contributed to molecular diffusions. Abstract: The design and synthesis of hierarchical self-assembled 2D-channel silica (2D-CS) with mesoscopicshape control and developing of their application in catalysis has remained a challenge. Herein, we fabricated a series of 2D-CSx materials through the hierarchical self-assembly of curved lamellar micelles along with their derivative 2D channel catalysts (2D-CSx -NH2 -HPW) by grafting amino groups and immobilizing phosphotungstic acid. These catalysts exhibit highly effective oxidative-adsorptive desulfurization (OADS) performance owing to their accessible open-transport channels. A novel theory that the stacking of curved lamellar micelles is similar to that of wrinkled-papers was proposed to explain the hierarchical self-assembly mechanism of the 2D-CS materials, which follows the "short-range order, long-range disorder" rule. Systematic characterizations and experiments indicated that the size and specific surface area of 2D-channel catalysts jointly determine their OADS performance. Most importantly, the 2D-channel catalysts show the highest removal efficiency of DBT when compared with 0D and 1D materials, which was ascribed to their facilitation of molecular diffusion owing to their accessible open-transport channels. The optimal 2D-channel catalysts (2D-CS4 -NH2 -HPW) exhibited excellent desulfurization performance despite omitting the extraction step, and the removal efficiency of DBT reached 99.72% in 5 min at 60 °C, much faster than previously reported mesoporous-catalyst-supported heteropoly acids. In addition, the OADS activity of typical sulfur compounds in the presence of the 2D-CSx -NH2 -HPW catalyst was investigated, and the sulfur removal efficiency was found to decreases in the following order: DBT > 4, 6-DMDBT > BT > n-DDM. The 2D-channel catalyst also exhibits excellent recyclability without significant loss of OADS activity after 10 cycles of reactions. This work provides a strategy for constructing 2D-channel catalysts for efficient desulfurization, demonstrating the potential of 2D-channel materials in catalytic applications.